2009
DOI: 10.1007/s10620-009-0742-3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Complicated Gastroesophageal Reflux Disease and Barrett’s Esophagus Among Racial Groups in a Multi-Center Consortium

Abstract: Aims The Clinical Outcomes Research Initiative database was used to evaluate ethnic trends in complicated reflux disease and suspected Barrett’s esophagus among various racial groups. Methods Endoscopic findings for procedures performed January 2000–December 2005 for any indication and for reflux-related indications were reviewed by racial group. Results Of 280,075 procedures examined, Hispanics were the most likely to have esophagitis (Hispanic 19.6%, white 17.3%, black 15.8%, Asian/Pacific Islander 9.5%,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(32 citation statements)
references
References 36 publications
3
29
0
Order By: Relevance
“…Recent work from the CORI database indicates that nHw are more likely to have a hiatal hernia and esophageal stricture than AA patients [16]. Other investigators have observed that hiatal hernia was associated with an increased risk of LSBE [14].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Recent work from the CORI database indicates that nHw are more likely to have a hiatal hernia and esophageal stricture than AA patients [16]. Other investigators have observed that hiatal hernia was associated with an increased risk of LSBE [14].…”
Section: Discussionmentioning
confidence: 98%
“…The subject of racial and ethnic discrepancies in the BE frequency has been addressed in prior studies [8][9][10][11][12][13][14][15][16]. However, risk ratios for the presence of histologic BE in AA has been reported less frequently [8,[14][15][16]. In two studies from the Clinical Outcomes Research Initiative (CORI) endoscopic database, odds ratios for the presence of BE were reported [8,16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A lower incidence of BE has been described in Hispanic Americans compared with the non-Hispanic white population, but whether BE in such patients follows a different natural history is incompletely understood. 30,31 As noted in the Methods section, 16 patients were excluded from the primary analysis because they did not have adequate follow-up. These patients had significantly longer-segment BE and required more ablative sessions than the study cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Barrett's oesophagus is a metaplastic change, following injury caused by reflux of acid and bile, in which one kind of fully differentiated cell replaces another [9]. Principal risk factors for BE development include duration of gastroesophageal reflux disease (GERD), hiatal hernia, male sex, family history of BE, obesity and cigarette smoking while CagA+ Helicobacter pylori colonization, regular aspirin or nonsteroidal anti-inflammatory drug use as well as African American race are associated with decreased risk [10][11][12][13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%